Assessing Variability in Vascular Response to Cocoa With Personal Devices: A Series of Double-Blind Randomized Crossover n-of-1 Trials - Bapir, Mariam; Campagnolo, Paola; Rodriguez-Mateos, Ana; Skene, Simon S.; Heiss, Christian (Frontiers in Nutrition, 2022)
Controlled clinical intervention studies have demonstrated that cocoa flavanols (CF) can decrease blood pressure and arterial stiffness in healthy humans, although a large variability in the effect size across trials has been reported. Here, we evaluated intra- and inter-individual variability of responses to CF in everyday life using a series of n-of-1 trials in healthy free-living individuals with normal blood pressure carrying personal devices. Eleven healthy young humans participated in a repeated cross-over randomized controlled double-blind n-of-1 trial. On eight consecutive days, each volunteer consumed on alternating days 6 CF capsules (862 mg CF) on four days and 6 matched placebo capsules (P, 0 mg CF/day) on another 4 days in one of two randomized sequences (CF-P-CF-P-CF-P-CF-P or P-CF-P-CF-P-CF-P-CF). On each day the capsules were taken at the same time in the morning with breakfast after baseline measurements. Each subject was provided with an upper arm blood pressure monitor and a finger clip that measures pulse wave velocity (PWV). Measurements of blood pressure, heart rate and PWV were taken at least hourly over 12 hours during the day by the participants. On the first 2 days measurements were performed under supervision to provide training. The overall mixed model analysis showed that CF significantly decreased 12 h systolic blood pressure and PWV by -1.4±0.3 mmHg and - -0.11±0.03 m/s, respectively. Peak effects were observed within the first 3 hours (1.5 h SBP: -4.9±2.2 mmHg, PWV: -0.32±0.17 m/s)and again after 8 h post ingestion. Large inter-individual variation in responses was found (intra-cluster correlation coefficients [ICC]: 0.41, 0.41). When analysing single individuals’ datasets, there was also considerable between-day variation in individual responses that varied greatly between subjects (ICC: 0-0.30, 0-0.22, 0-0.45). Effect sizes inversely correlated with baseline blood pressure values both between-- and within-subjects. The data confirm that cocoa can decrease blood pressure and arterial stiffness in everyday life when elevated within the normal range. The large inter- and intra-individual variation in responses call for more personalized nutritional intervention strategies.